Effect of PCI on ophthalmic artery hemodynamics in patients with acute coronary syndrome - Liu, Wen-long; Wu, Lan-ting; Wang, Jia-lin; Sun, Jiao; Cheng, Xue-ru; Zhou, Zhuo-hua; Guan, Jia-xin; Wang, Yan-ling; Meng, Zhao-yang (Frontiers in Medicine, 2024)
Purpose We aimed to explore the effects of percutaneous coronary intervention (PCI) on the ophthalmic artery (OA) hemodynamics in patients with acute coronary syndrome (ACS). Methods A total of 73 participants (Group0: healthy controls, Group1: Patients with ACS underwent PCI < 3 months, Group2: Patients with ACS underwent PCI ≥ 3 months) were enrolled. Computed tomographic angiography images were used to construct three-dimensional models of participants' OAs. Numerical simulations based on computational fluid dynamics were used to acquire hemodynamic parameters. Results The angle between the OA and internal carotid artery in Group2 was significantly larger compared with Group0 and Group1 (P = 0.003 and P = 0.044). Hemodynamic simulation showed a significantly slower OA blood velocity in Group1 than in the control (P < 0.001) and Group2 (P = 0.033). Lower wall shear stress was found in Group1 than that in control (P = 0.040). Patients after PCI had a higher wall pressure than healthy controls (P = 0.012 and P = 0.004). Mass flow ratios were decreased in Group1 and Group2 (P = 0.021 and P = 0.002). The hemodynamic parameters of OA were correlated with several clinical indicators. Conclusions The OA blood flow velocity of patients with ACS after PCI initially slowed down, which increased the risk of plaque formation, and then showed an increasing trend. There was a correlation between OA hemodynamic parameters and clinical indexes related to cardiac stress. Ischemia-reperfusion injury and changes in blood flow status after PCI may affect OA morphology and hemodynamics, leading to ocular lesions. Trial registration ChiCTR2100050428.